Properties of polymer modified concrete in fresh and hardened state - Ion, Ioana Mirabela (2013)
It was carried out a study on the properties of polymer modified concrete (PCM) in fresh and hardened state. It was used three types of polymers: epoxy resins, polyurethane and methylcellulose in different percentages and different water cement ratio. The main objectives was to improve workability and rheological behavior of these mixtures in fresh state and mechanical strength tests on hard concrete. Has been investigated the polymer influence on compression strength and flexural strength and analyzing the time evolution of these strengths and participation of polymer in the microstructure formation.